Comparative assessment of fouling scenarios in an axial flow compressor (Conf) - Templalexis, Ioannis; Pachidis, Vassilios; Hasani, Azamar (American Society of Mechanical Engineers (ASME), 2021)
It is commonly accepted that fouling degrades severely axial compressor performance. Deposits build up throughout the compressor’s operating life, causing a decrease in its delivery pressure, efficiency and flow capacity. Researchers have also concluded that the presence of wet contaminants and/or high air humidity, plus the quality of air filtration systems, have a far greater impact on fouling rates, than engine specific fouling susceptibility factors [1]. The size of airborne particles ingested into the engine is primarily controlled by the presence of a filtration system. On the other hand, the particle deposition rate and the fouling patterns formed on the blade surfaces are greatly affected by the “stickiness” of the blade surfaces which in turn is affected by the moisture level of the incoming air. Compressor geometry, size and operating point would affect far less the rate of contaminants built up on the wetted surfaces and they would affect even less the exact location on compressor walls and blade surfaces. The current study identifies four basic operating scenarios which refer to the same compressor, in order to put forward a comparative assessment as to how the factors mentioned above, affect the compressor performance through the fouling mechanism. Scenarios were formed out of the possible combinations regarding the presence of a filtration system and the level of humidity. These were: i) Filtered - dry air, ii) Filtered - humid air, iii) Unfiltered - dry air, and iv) Unfiltered - humid air. These scenarios will eventually reproduce four completely different situations regarding the quality of the incoming air and subsequently, four different fouling regimes for the compressor operating downstream. Data to support the impact of each reported incoming air condition on compressor wetted surfaces, are based on experimental findings collected from a thorough literature review. A fixed operating period was set for all cases. Prescribed requirements of the computational tool selected to build the compressor model were; i) low computational power since several runs had to be performed in order to cover the assumed time period, and ii) ability to introduce the imprint of various fouling patterns on compressor blades, into the performance of the compressor. SOCRATES, an in-house two-dimensional, streamline curvature-based, through-flow computational tool, meets these requirements and it was used for this study. A fully customizable empirical model, recently introduced in the code, takes into account various aspects of fouling such as the surface roughness level, the flow blockage and the altered deviation angle at the exit of the blade row. A coverage factor was introduced which takes into account the location and the extent of fouling onto the blade surfaces.
Keywords: turbofan engine; fouling; streamline curvature